Network Diversity Multiple Access in Rayleigh Fading Correlated Channels with Imperfect Channel and Collision Multiplicity Estimation - Robles, Ramiro (2016)
24th Telecommunications Forum TELFOR 2016 (TELFOR 2016). 22 to 23, Nov, 2016. Serbia.